Cetacean diversity of Mauritius - Webster, Imogen; Cockcroft, Vic; Cadinouche, Adele; Huggins, Annette (J. Cetacean Res. Manage., 2020)
There is limited information concerning the cetaceans inhabiting the coastal waters of Mauritius. This document details the sightings of cetaceans encountered during April 2008 – September 2014. Boat-based surveys were conducted throughout the year, primarily focusing on spinner and bottlenose dolphin populations that are important for the local dolphin-watching industry. More than 1246 hours over 749 days of surveys were spent searching for cetaceans. All cetaceans encountered were recorded. During 2013 and 2014, dedicated diversity surveys were conducted and 2443.6km of search effort was covered around the islands. The encounter rate was 0.025 cetacean sightings/km. Over the total study period 13 species were recorded from 1459 sightings. Species included: Megaptera novaeangliae, Stenella longirostris, Tursiops aduncus, Tursiops truncatus, Globicephala macrorhynchus, Stenella attenuata, Physeter macrocephalus, Mesoplodon densirostris, Feresa attenuata, Peponocephala electra, Grampus griseus and Ziphius cavirostris. In addition, there were strandings of Kogia sima and Ziphius cavirostris. The most common species encountered were spinner dolphins, Indo-Pacific bottlenose dolphins, humpback whales and sperm whales. As expected only humpback whales showed any seasonality in monthly encounter rates (Kruskal-Wallis H = 42.39, Hc = 54.25, p < 0.001). The overall Shannon diversity index was 0.58 (95% CI 0.57–0.60) though this ranged between 0.77 in 2009 to 0.25 in 2014. The Shannon index value for the diversity study was 0.83 (95% CI 0.74–0.91). This study demonstrates the richness of the waters around Mauritius and the importance of the area for beaked whales, migrating humpback whales and the presence of resident sperm whales.